2020
DOI: 10.1080/21501203.2019.1710303
|View full text |Cite
|
Sign up to set email alerts
|

Newly emerging diseases of marine turtles, especially sea turtle egg fusariosis (SEFT), caused by species in the Fusarium solani complex (FSSC)

Abstract: Sea turtles are presently considered severely endangered species that are historically threatened by many environmental factors. Recently, additional threats to sea turtles from two pathogenic species of fungi in the Fusarium solani species complex (F. falciforme and F. keratoplasticum) have been identified. These species infect marine turtle eggs, causing sea turtle egg fusariosis, and kill their embryos, with recent reports of hatch-failure in seven globally distributed species of endangered sea turtles (Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 55 publications
2
32
0
3
Order By: Relevance
“…Specifically, most isolates corresponded to F. keratoplasticum (lineage FSSC 2), a soil-borne species globally distributed. Notably, previous studies have reported that this and other species of the FSSC constitute a real threat to sea turtle nests worldwide, especially to those subject to environmental stressors, among others, inundation and clay/silt composition of nests [ 28 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, most isolates corresponded to F. keratoplasticum (lineage FSSC 2), a soil-borne species globally distributed. Notably, previous studies have reported that this and other species of the FSSC constitute a real threat to sea turtle nests worldwide, especially to those subject to environmental stressors, among others, inundation and clay/silt composition of nests [ 28 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium infection is considered as the primary driver of declining turtle populations around the world [ 39 ]. The sea turtle egg fusariosis (STEF) is an emerging disease and is responsible for egg mortality in sea turtles around the world, where most of the cases are related to F. keratoplasticum and F. falciforme [ 40 , 41 , 42 , 43 , 44 , 45 ]. During the embryonic development, the eggs spend an extensive amount of time buried under the sand in a sticky and warm consistent temperature, and it has been suggested that these conditions support the development of soil-borne fungi such as Fusarium [ 41 , 45 ].…”
Section: Fusarium and Animal Diseasementioning
confidence: 99%
“…They can infect plants (Coleman et al, 2009), animals (O'Donnell et al, 2016), and humans (Horn et al, 2014). Fusarium keratoplasticum and Fusarium falciforme, two terrestrial FSSC species, have caused fusariosis of endangered sea turtle eggs (Sarmiento-Ramirez et al, 2014;Gleason et al, 2020). F. keratoplasticum and Fusarium petroliphilum are the two FSSC species most frequently isolated in the clinic (Herkert et al, 2019;James et al, 2020).…”
Section: Introductionmentioning
confidence: 99%